Characteristics of Community-based Rural Water Supply System in Jambon Village, Kulon Progo City - Lutfia Lutfia; Uswatun Khasanah Amalia; Hairani Ani (BIO Web of Conferences)
According to Government Regulation of the Republic of Indonesia Number 122 of 2015 concerning Drinking Water Supply Systems, the Government is responsible for ensuring public access to drinking water. However, several areas in Yogyakarta are experiencing water shortages. One solution to overcome this situation is to build a community-based rural clean water supply system, called SPAMDes. Each SPAMDes has different characteristics regarding its management and maintenance system because it is managed directly by village community groups. This research aims to examine the characteristics of SPAMDes Tirto Sari Ponces which is located in Nanggulan sub-district, Kulon Progo Regency starting from management, services and network infrastructure conditions. It is hoped that this research can become supporting data for researchers, the government and related agencies so that they can plan an effective rural development program The methods used in this study are field surveys, questionnaires, and interviews. Based on the analysis of the data obtained, the condition of the SPAMDes network infrastructure has not been well maintained. The operational system is still relatively simple and not comprehensive. The level of consumer satisfaction with water quality, water quantity, services provided, information media used in services, and the rates set are considered satisfactory.